(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
Thanks to the agreement between the Università degli Studi di Milano and the General Direction of Antiquities and Museums of Damascus, the Syro-Italian Archaeological Mission in Palmyra (PAL.M.A.I.S.) has been working in Tadmor-Palmyra (Syria) since 2007, under the direction of Prof. Maria Teresa Grassi. The fieldwork, devoted to the study of the domestic architecture of the roman city in a significant area, the South-West Quarter, where a stratigraphical excavation around the Peristyle Building has been carried out - stopped in 2011. The researches are now focused on the architecture and the material culture in order to publish the final report.